PENGANGKAAN (KUANTIFIKASI) PERIKSAAN PULASAN GRAM DI BERBAGAI JENIS BAHAN PEMERIKSAAN - Adhi Kristianto Sugianli; Ida Parwati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
In a clinical microbiology laboratory the Gram staining is used to classify bacteria on the basis of their forms, sizes, cellularmorphologies, and Gram reactions. Additionally it is a critical test for rapid presumptive diagnosis of infectious agents and serves toassess the quality of clinical specimens. Several methods of Gram staining quantification are already applied: Canadian Coalition forQuality in Laboratory Medicine (CCQLM), Clinical Microbiology Proficiency Testing (CMPT), and World Health Organization (WHO).Each method consists of several criteria for quantification and its interpretation, such as neutrophil cell (polymorphonuclear cells),squamous epithelial cell, and number of microorganisms. Those methods aren't limited in sputum specimen, but also could be used forother specimen such as urine, vaginal discharge, and other body fluids. These methods are also could be used as screening for specimenbefore it is continued into further testing. Even though there is several limitation for each method, quantification method of Gramstaining could be provide better diagnostic value in microbiology laboratory as an early detection in the examination to get betterdiagnosis as well as treatment.